Successful β cells islet regeneration in streptozotocin-induced diabetic baboons using ultrasound-targeted microbubble gene therapy with cyclinD2/CDK4/GLP1 - Shuyuan Chen, Raúl A.; Bastarrachea, Raúl A.; Voruganti, Venkata Saroja; Frost, Patrice A.; Nava González, Edna Judith; Arriaga Cazarez, Jixji Chen; Huang, Pintong; DeFronzo, Ralph A.; Comuzzie, Anthony G.; Garyburn, Paul A. (2014)
Both major forms of diabetes mellitus (DM) involve β-cell destruction and dysfunction. New treatment strategies have focused on replenishing the deficiency of β-cell mass common to both major forms of diabetes by islet transplantation or β-cell regeneration. The pancreas, not the liver, is the ideal organ for islet regeneration, because it is the natural milieu for islets. Since islet mass is known to increase during obesity and pregnancy, the concept of stimulating pancreatic islet regeneration in vivo is both rational and physiologic. This paper proposes a novel approach in which non-viral gene therapy is targeted to pancreatic islets using ultrasound targeted microbubble destruction (UTMD) in a non-human primate model (NHP), the baboon. Treated baboons received a gene cocktail comprised of cyclinD2, CDK, and GLP1, which in rats results in robust and durable islet regeneration with normalization of blood glucose, insulin, and C-peptide levels. We were able to generate important preliminary data indicating that gene therapy by UTMD can achieve in vivo normalization of the intravenous (IV) glucose tolerance test (IVGTT) curves in STZ hyperglycemic-induced conscious tethered baboons. Immunohistochemistry clearly demonstrated evidence of islet regeneration and restoration of β-cell mass.